Pastoral Counter-Conducts: Religious Resistance in Foucault’s Genealogy of Christianity - Chrulew, Matthew (Sage Publications Ltd., 2014)
The internal resistance to religious forms of power is often at issue in Michel Foucault’s genealogy of Christianity. For this anti-clerical Nietzschean, religion is, like science, always a battle over bodies and souls. In his 1978 Collège de France lectures, he traced the nature and descent of an apparatus of “pastoral power” characterized by confession, direction, obedience, and sacrifice. Governmental rationality, both individualizing and totalizing, is its modern descendant. At different moments, Foucault rather infamously opposed to the pastorate and governmentality such ethico-political spiritualities as the Iranian Revolution and ancient Greek ascesis, but he also took care to identify numerous forms of resistance specific and internal to Christianity itself. His lecture of 1 March 1978 outlined five examples of “insurrections of conduct”: “eschatology, Scripture, mysticism, the community, and ascesis.” I will detail Foucault’s analysis of pastoral counter-conducts, and explore how he sets up the nature and stakes of this tension within Christianity and its secular kin.